MODERNIZATION IN JAPAN: STAGES AND DIRECTIONS OF REFORMS - А. Рүстемовa; Н.Ә. Алдaбек; Е.А. Ахaпов (Journal of Oriental Studies, 2019)
The modernization of Japan, conducted after the «opening» of the country in 1868, is of high interest for the scientific society in the field of further understanding of the mechanisms that enabled the country to reach a high level of development. At the end of the XIX century - early XX century Japan’s economic growth rates exceeded the average indicators of other developed countries of the world. At present, the Japanese economy is the third economy in the world, which is almost 25% more than the next German economy, and is equal to economies of India and England combined, which are the following countries on this list. Despite the fact that modernization in the country was continuous, there are two main stages of it: modernization in the Meiji period and in the post-war period in the conditions of democratization. The modernization project has affected all areas of the country’s life. Its distinctive feature is the intro- duction of new reforms (economic, political, social, etc.) while maintaining the traditional foundations. The purpose of this work is a comprehensive analysis of the modernization processes that took place in Japan over the last century and a half. As a result of the elaborated and effectively implemented measures of the comprehensive modernization plan of the country, Japan has become the most developed country in the Asia-Pacific region, which successfully competes in the economic and technological spheres with the West and is in many ways a model of modernization for other Asian countries. Key words: Japan, modernization of Meiji Ishin period, modernization of post-war period, reforms, model for catch-up development.